Aesthetics of Ecoprint with Quilting Technique Application on Fashion Products - Agustin, Pingki Aulia; Arrsyi, Esty Nurbaity (VISIORA: Journal of Creative Industries and Vocational Innovation, 2025)
This research aims to obtain ecoprint aesthetic results of the application of quilting techniques on fashion products as assessed by 4 expert panelists based on A.A.M Djelantik's aesthetic theory with indicators of form/appearance, weight/content and appearance/presentation. The research method uses quantitative descriptive with pre-experimental design, one shot case study and data analysis techniques use descriptive statistics. The fashion products made are in the form of 5 vest designs with different design placement. The data collection technique uses mixed lifting. The overall aesthetic results based on aspects of form/appearance, weight/content and appearance/presentation obtained a percentage score of 90% in the very good category. The shape/form indicator consists of design elements and principles, namely shape, color, texture, harmony, rhythm and proportion, which received the highest percentage score of 91%. The weight/content indicator is based on ideas, the source of inspiration used is "Poppy Fields" which received the second highest score of 90% in the very good category. The appearance/presentation indicator based on means/media received the lowest score of 89% in the very good category. The product with the highest rating was design 2, namely 95%, and the lowest score was obtained by designs 3 and 4, namely 88%, with a very good category among the five design products.